Bertiera acutiflora (Rubiaceae, Bertiereae), a new combination based on the overlooked Psychotria acutiflora - Andreas Berger (PhytoKeys)
Psychotria acutiflora was described in 1830 by de Candolle in his Prodromus, and was based on a single collection by Thaddäus Haenke from near Guayaquil, Ecuador. Although the identity of the name has never been studied since its original publication, it is currently treated as a species endemic to Ecuador. It is shown here that the type of the name belongs to Bertiera procumbens, which was described much later. Therefore, the new combination Bertiera acutiflora is provided here for the Columbian and Ecuadorian endemic and a lectotype is designated for the name.